PENGARUH pH TERHADAP AKTIVITAS PENISILIN G ASILASE YANG DIHASILKAN ISOLAT BAKTERI DARI AIR BATANG KURAO KOTA PADANG - Desriyati, Desriyati; Fifendy, Mades; Megahati Siregar, RRP (STKIP PGRI Sumbar, 2013)
Many pathogenic microorganisme were found to be resistant to penicillin, to prevent the occurrence of penicillin resistance is then produced semisynthetic penicillins, basic materials used for the manufacture of semisynthetic penicillins a 6-aminopenisilanat acid (6-APA). 6-APA is the result of hydrolysis of penicillin by the enzyme activity of penicillin G acylase, Penicillin G acylase produced by various microorganisme, such as fungi and bacteria. This study aimed to determine the effect of pH on the activity of penicillin G acylase resulting bacterial isolates from stem water Kurao Padang. This study was conducted from October 2012 to January 2013 in the Laboratory Kopertis X Padang region of West Sumatra. This type of research is that the experimental treatment pH variation between (6,5 - 8,0) of the PGA activity resulting bacterial isolates and calculate the resulting enzyme activity using the method of Kornfeld is a method that has a high sensitivity and fast in detecting compounds 6-aminopenisilanat acid (6-APA). Results showed pH affects the activity of PGA by bacterial isolates from water with pH variation stems Kurao PGA 0.0101 6.5 activity units / ml, at pH 7.0 activity PGA 0.0269 units / ml, where as at pH 7.5 PGA activity of 0.0200 units / ml, and the pH 8.0 activity PGA 0.0064 units / ml. Based on the research that has been done can be concluded that the activity of Penicillin G Acylase resulting bacterial isolates from water Kurao Batang Padang has an optimum pH of 7.0 with enzyme activity (AE) PGA 0.0269 units / ml.